2018
DOI: 10.3390/su10114273
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to a New Supplementary Cementing Material: Arundo donax Straw Ash

Abstract: Arundo donax is a plant native to Asia and is considered an invader species in the Mediterranean region and many tropical zones in the world. These invader plants can be collected to produce a biomass, which can be converted to ash by combustion. The scope of the study is to assess the use of these ashes (Arundo donax straw ash [ADSA]) as supplementary cementing material due to their relatively high silica content. Electron microscopy studies on dried and calcined samples of different plant parts (cane, sheath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…24%), indicating the alkaline nature of the samples. The elements detected in the A. donax ashes in this work are practically the same as those reported by other authors, although their A. donax leaf ash contained a small amount of Al ( Payá et al., 2018 ), but no sodium (Na).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…24%), indicating the alkaline nature of the samples. The elements detected in the A. donax ashes in this work are practically the same as those reported by other authors, although their A. donax leaf ash contained a small amount of Al ( Payá et al., 2018 ), but no sodium (Na).…”
Section: Resultssupporting
confidence: 90%
“…Shakoor et al (Shakoor et al, 2016) examined phytoliths of the A. donax leaf, and reported the same elements detected herein, except S and P. In addition, these authors found nitrogen (N) and Al (Table 2). In the study of Payáet al (Payáet al, 2018) the phytoliths appeared to contain only six elements (Table 2).…”
Section: Chemical Compositionmentioning
confidence: 92%
See 1 more Smart Citation
“…The directions which are considered primarily when selecting the technology of ashes management are the possibility of fertilizer use. Moreover, they can be used in the production of building materials [7], road construction [8], and mining [9]. However, the choice of the direction of use must be preceded by an examination of basic properties of ashes in order to specify the direction of analysis of the selected solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of biomass ash have been attracting a lot of attention recently in various fields, such as farmland fertilizer [1][2][3], construction material [4,5], adsorbent material [6,7], production material of ceramics, and raw material of metal recovery [7,8]. In all these applications, the soil application as a green, cyclic, and sustainable way has a huger potential and better prospect [9,10].…”
Section: Introductionmentioning
confidence: 99%